Interview 8 - Abubakari, Yushawu
This file contains the interview notes with Bossman. Bossman (pseudonymize) is 27 years and a basic school teacher. Bossman Parents died and he’s taking care his 4 younger siblings. Bossman has been in the scamming industry for 4 years. Bossman is a leader and has collaboration with other scammers in Nigeria, Cameroon, and USA. Bossman has those working under him at the local level. The interview was conducted at Bossman’s residence